Biomechanical basis of human movement - Hamill, J.; Knutzen, K. M. (Wolters Kluwer Health, 2009)
Integrating basic anatomy, physics, calculus, and physiology, this fundamental text offers you a solid introduction to the study of biomechanics. By focusing on movement patterns of muscle groups rather than individual muscles, this text provides a holistic understanding of human movement.